Membangun Kolaborasi Antara Orang Tua dan Anak melalui Permainan Edukatif mengisi Air ke Dalam Botol di TK Al Ghifari - Anggun Apriliani; Nanda Putri; Nesya Azzahara; Farisa Fauziyyah; Desi Hulandari; Winda Sherly Utami; Indryani (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIM Sinjai, 2025)
This community service activity aims to build togetherness and cooperation between parents and children through an educational game of filling water bottles at Al Ghifari Islamic Kindergarten. This activity was carried out using a participatory approach that directly involved parents and children in every stage of the activity, from preparation, implementation, and evaluation. Before the game began, parents were given a brief explanation regarding the importance of closeness between parents and children in supporting early childhood development. After the presentation of the material, the activity continued with a game of filling water bottles, which was played together by parents and children. This game is a simple yet meaningful way to build emotional closeness. Throughout the activity, children appeared enthusiastic and tried to complete the game with parental support. Through this interaction, parents were able to better understand their children's abilities and build warmer and more positive communication. The results of the activity show that simple games can be an effective medium for strengthening parent-child relationships and supporting early childhood development in a fun way.